Multidisciplinary Team Meetings About a Patient in Primary Care - Sabine Van Houdt MSc (Journal of Primary Care & Community Health, 2011)
Multidisciplinary team meetings (MTM) about a patient are a way to coordinate fragmented care. The Minimal Data Set/Resident Assessment Instrument (MDS/RAI) is a tool to prepare and support these meetings. Methods : An exploratory, qualitative study was used to examine the factors that influence the need for an MTM and to determine the value of MDS/RAI supporting the MTM. Results : Key elements are awareness of the health care professionals that “something is wrong” and the presence of sufficient family caregivers with enough capacity. The MDS/RAI is an aid because registration provides all health care professionals with the same type of preparation, allows possible blind spots to be discovered, and provides structure to the multidisciplinary meeting. Multidisciplinary meetings were found to contribute to sharing of information, knowledge, goals, and mutual respect. Conclusion : The evaluation of the patient’s care needs by MDS/RAI registration, performed by health care professionals involved in the care, and discussion of the results leads to more efficient MTMs.